Meta-Analysis of the Influence of Obesity on the Incident of Preeclampsia in Pregnant Women - Verasita, Prissy; Orchida, Tidi; Fatihah, Enjeli Wally; Atmojo, Joko Tri; Widiyanto, Aris (Indonesian Journal of Global Health Research, 2024)
Preeclampsia is the onset of high blood pressure accompanied by proteinuria and edema in pregnancy after 20 weeks of gestation or after the postpartum period. Obesity has been widely studied as a risk factor for preeclampsia. This study aims to estimate and analyze the impact of obesity on the incidence of preeclampsia in pregnant women.This research is a systematic review and meta-analysis research using the PRISMA diagram and using 4 articles from 2015 to 2020. Article searches were carried out based on the PICO Model eligibility criteria. P= Pregnant women; I=Obesity; C= Not obese; O= Preeclampsia. The articles used come from 1 database, namely: Google Scholar. With keywords including "Obesity" AND "Preeclampsia" AND "Pregnant Women" AND "Cross Sectional".Articles were analyzed using the PRISMA diagram and the Review Manager 5.3 application. 4 articles with a cross-sectional study design will be used as a source for meta-analysis influence of obesity on the incidence of preeclampsia in pregnant women. Shows that obesity increases the possibility of preeclampsia in pregnant women. Obese pregnant women have an increased risk of preeclampsia by 2.04 times compared to non-obese pregnant women (aOR= 2.04; 95% CI= 1.90 to 2.19; p=0.001), and the results are statistically significant. Meta-analysis of 4 cross-sectional studies concluded that obesity in pregnant women increases the occurrence of preeclampsia.